Article review: Cost effectiveness analysis of antihypertensive amlodipine compared to captopril in health care facilities - Windi Astuti; Moh. Rasyid Kuna; Nanda Sayyida Begum; Nur Wahyu Nadila Ginoga; Muhammad Anugrah Sugeha (Journal of Midwifery and Nursing, 2025)
Hypertension, also known as high blood pressure, is a disease characterized by an increase in systolic blood pressure exceeding 140 mmHg and diastolic blood pressure exceeding 90 mmHg, in several measurements with a time of five minutes and with sufficient rest.  The purpose of this study is to determine the cost effectiveness of hypertension therapy by using a comparison of amlodipine and captopril drug therapy in health service facilities. The method chosen was a literature study taken from journals and the results of previous research from various references related to the cost-effectiveness of antihypertensive therapy. Based on several journal literature or scientific publications that have been researched regarding the cost-effectiveness of amlodipine antihypertensive therapy compared to captopril, the results show that amlodipine has a higher effectiveness compared to captopril based on ACER and ICER values from several previous studies. Based on 10 literatures that have been analyzed, 7 literatures state that amlodipine antihypertensive is more Cost-Effective compared to captopril antihypertensive.